Efektifitas Pemberian Posisi Dan Nesting Terhadap Perubahan Status Hemodinamik Pada Bayi Prematur Di Ruang Perinatologi: Effectivity Of Positioning And Nesting On Alteration of Hemodynamic Status In Premature Infants In Perinatology Unit - Sutanto, Olivia Regina; Utami, Tuti Asrianti (Jurnal Abdi Keperawatan dan Kedokteran, 2025)
Premature infants are high risk babies that are susceptible to the risk of morbidity and mortality, because of the susceptibility further care are required. Positioning and nesting, which is one of the interventions from developmental care model is useful for supporting the development of premature infants. This study aims to ensure the effect of positioning and nesting on alteration of hemodynamics status in premature infants in the perinatology unit. Case study using 6 respondents of premature infants in perinatology units at RS X Jakarta with observational method. The samples were done to six premature infants with low birth weight below 2500 grams, from May 26 to June 19, 2025. Data was collected with before and after given intervention changing sleeping positions every 2 to 3 hours, and given nesting position afterward for infants. Collected datas were focused on hemodynamic stats (temperature measurement, heart rate, respiration rate, and oxgen saturation) which will be monitored on observation sheet. Observations were taken when the premature infants were given lateral right or left, supination, semipronation and nesting. After being given interventions to six premature infants, there was a decrease on heart rate and an improvement on the oxygen saturation, the implementation that were given can maintain stability on hemodynamic status on premature infants. Results of the observations in this study, concluded that there is positive effect on improvement and stability on hemodynamic status with six premature infants. This intervention is expected to be an integral part of nursing care for premature infants.